The Influence of e-Content on Academic Performance and Retention Ability in Learning Mathematics among High School Students - Solomon Four Equivalent Group of Experimental Design - Saravanakumar AR, Prabakaran B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to find out the more influence on the academic performance and the retention ability after receiving the subject concept through pedagogical methods such as conventional and modern methods of teaching. The investigator used the pre, the post and the retention tests for Solomon Four- Group Design of the experiment in this research. The convenient sampling technique which was adopted by selecting a sample of 20 students of the Ninth standard for each group was assigned to the conventional and modern method of teaching. The e-content development module and a standardized researcher’s achievement test were developed by the researcher under the guidance of the research supervisor based on the Mathematics subject portion as set theory including skills of drawing the Venn diagram. Levene, ANOVA, Bonferroni, ω2, r2, Effect Size (d) and Gain Ratio tests are used for statistical analysis and interpretation of achievement and retention scores (data) and the results are discussed in this paper along with the findings and recommendations.